Anterior Cervical Spine Surgery in Fracture Dislocations of the Cervical Spine: Clinical Outcome - Thapa, Bishnu Babu; Shah, Rajesh Pratap; Rana, Sushil; Chand, Pankaj; KC, Bachchhu Ram (Nepal Orthopaedic Association Journal, 2016)
BACKGROUND: Anterior cervical discectomy and fusion (ACDF) is the one of the commonly performed procedures in the treatment of pathology related to cervical discs. ACDF has been shown to achieve successful stabilization in about 95% of cases. The anterior approach to the cervical spine was initially described by Smith, Robinson, Bailey, Badgley and Cloward. These techniques have been refined with the use of internal fixation with or without bone implants. MATERIAL AND METHODS: This prospective study was conducted in Shree Birendra Hospital, Chhauni from August 2012 to September 2015. Twenty nine patients operated for fracture dislocations of cervical spine were included. All patients were operated with the left side Smith and Robinson approach. The cervical spine level was confirmed with the help of image intensifier after putting a bent needle at the disc level. Iliac crest tricortical graft was harvested and put into the disc space and fixed with an anterior cervical plate. All patients were discharged after removal of stitches at 2 weeks post-op. They were followed up at 6 weeks, 3 months and 6 months, and then yearly upto 2 years. At each visit, X-rays were taken to evaluate the progression of fusion and maintenance of sagittal alignment. RESULTS: There were 29 operated patients - either ACDF or corpectomy and fusion. Out of 29 patients, 26 were male. 19 patients had incomplete cord injury, 5 patients had complete cord injury and 5 had intact neurology. All incomplete cord injury patients had improvement in their neurology by grade 1-2 after surgery. One patient developed a sacral bed sore and one died after surgery. The mean VAS score for pain improved from 6±2 to 2±1 post operatively. CONCLUSION: Anterior cervical spine surgery improves the neurology and pain scores m traumatic cervical spine patients with a low rate of complications.